Policy Trilemma and Interest Rate Behaviour in Nigeria (2018)
Policy makers face trade-off in dealing with exchange rate management, mo- netary independence and concerns about capital mobility simultaneously. This study empirically examines the effects of Nigeria's trilemma policy path on interest rate using data spanning from 1997:Q1 to 2017:Q3. It equally in- corporates the role of external reserves in buffering these effects. Stationar- ity of the series were ascertained with Zivot-Andrew (ZA) structural break unit roots test technique, while the bounds test cointegration approach was used to confirm the cointegrating properties of the variables. We found that capital mobility has significant effect on interest rate in the long run base- line model and could also be successfully buffered with external reserves to reduce interest rate. Additionally, our results show that although exchange rate stability and monetary independence do not independently affect inter- est rate, but their interaction with external reserves does. This implies that external reserve serves as an effective buffer if appropriately employed by the monetary authorities. The trilemma policy can be used to optimally reduce interest rate. Also, external reserves could serve as a tool for economic sta- bilization with appropriate combination with other relevant policy variables.